Cytokine Profile Alterations in Celiac Disease: Evaluation of IL-12, IL-6, and IL-4 - Beden, Murtada Wafi (Medical Science Journal for Advance Research, 2026)
Background: Dietary gluten can cause celiac disease (CD), in those who are genetically predispose. Celiac disease, which is an immune-mediated chronic enteropathy. Intestinal inflammation and disrupted cytokine production are hallmarks of the disease’s intricate immune mechanisms. This study considered serum levels of interleukins (12,6,and 4) in order to evaluate the cytokine report of people with celiac disease. Methodology: Thirty-five celiac disease patients were included in an observational/ cross-sectional study. The study was conducted between September 2024 and July 2025, at Al Nasiriyah general hospitals and the private clinics of the digestive system in ThiQar province. Demographic information were collected, including age, sex, history of immune-mediated disorders, and familial history. Cytokine levels were examined using enzyme immunosorbent assay ( Fine Test) ELISA kits. Results: Participants’ average age was 18.68 ± 4.08 years, and 57.1% of them were female. For IL-12, IL-6, and IL-4, the mean serum concentrations were 8.03 ± 3.55 pg/mL, 15.36 ± 5.91 pg/mL, and 3.85 ± 2.09 pg/mL, respectively. While IL-12 suggested Th1 immune pathway activation, elevated IL-6 levels suggested a strong inflammatory response. Th2-mediated anti-inflammatory activity was limited, as evidenced by the relatively lower levels of IL-4. Conclusion: These results lend credence to the idea that a Th1-dominant immune response with potent inflammatory signaling is the primary cause of celiac disease. Therefore, cytokine profiling may help monitor disease activity and help understand the immunopathogenesis of diseases.